XDR-Pseudomonas aeruginosa Outside the ICU: Is There Still Place for Colistin? - Paola Del Giacomo; Francesca Raffaelli; Angela Raffaella Losito; Barbara Fiori; Mario Tumbarello (MDPI AG, 2022)
Background: Pseudomonas aeruginosa represents, among the nosocomial pathogens, one of the most serious threats, both for the severity of its clinical manifestations and its ability to develop complex profiles of resistance; Methods: we retrospectively collected the data of 21 patients admitted to a tertiary-care University Hospital of Rome with infections due to XDR-P. aeruginosa isolates during the second half of 2020; Results: in our institution, the percentage of XDR-P. aeruginosa isolates is 3.1%. None of the patients was admitted to the intensive care unit at the moment of the infection's onset. Susceptibility to colistin was preserved in all the tested isolates. Rates of resistance to ceftolozane/tazobactam and ceftazidime/avibactam in these XDR strains were consistent; Conclusions: XDR-P. aeruginosa can be a threatening problem even outside the ICUs, especially in frail patients in wards with features of long-term acute care hospitals. In such a setting, ceftolozane/tazobactam and ceftazidime/avibactam should be administered with caution taking into account the microbiological susceptibility results. Colistin, even with its known safety and efficacy limits, could represent the only available therapeutic option due to its highly preserved susceptibility against XDR isolates of P. aeruginosa.